Neurotization of the human cornea – A comprehensive review and an interim report - Anubha Rathi; Nandini Bothra; Smruti R Priyadarshini; Divya S R Achanta; Merle Fernandes; Somasheila I Murthy; Anasua G Kapoor; Tarjani V Dave; Suryasnata Rath; Rajesh Yellinedi; Rambabu Nuvvula; Gautam Dendukuri; et al. (Indian Journal of Ophthalmology, 2022)
We present a comprehensive review of existing literature on surgical corneal neurotization (SCN) as a treatment modality for neurotrophic keratopathy (NK) with an interim report of seven cases where SCN was performed using the indirect approach and followed up till 18 months postoperatively to look for improvement in ocular surface, corneal sensations, and nerve regeneration by using in vivo confocal microscopy (IVCM). A literature search was performed for publications with keywords “corneal nerves,” “neurotization,” “esthesiometry,” “corneal anesthesia,” and “neurotrophic keratopathy.” All literature available till December 31, 2020 was reviewed and included to describe NK and its management options, particularly SCN. NK is associated with absent or reduced corneal sensations and is managed using a step-ladder algorithm ranging from medical management for symptomatic relief to surgical corneal neurotization. Both direct and indirect approaches of SCN have a favorable outcome with reduced surgical morbidity in the indirect approach using sural nerve graft. Post neurotization, corneal sensation recovery may take up to 3–6 months, while nerve regeneration on confocal microscopy can take as long as 6 months–1 year.